MBRS-12. A TRANSPOSON MUTAGENESIS SCREEN IDENTIFIES Rreb1 AS A DRIVER FOR GROUP 3 MEDULLOBLASTOMA. (4th December 2020) - Masihi, Meher Beigi; Lee, Catherine; Furnari, Grace A; Garancher, Alexandra; Wechsler-Reya, Robert J
Abstract: Medulloblastoma (MB) is the most common malignant childhood brain tumor. MB can be divided into four major subgroups – WNT, Sonic hedgehog (SHH), Group 3 (G3), and Group 4 (G4) – that exhibit distinct genetic alterations, gene expression profiles, and clinical outcomes. Patients with G3-MB have the worst prognosis, and a deeper understanding of this disease is critical for development of new therapies. Most G3-MBs express high levels of the MYC oncogene, suggesting that MYC plays an important role in tumorigenesis. To identify genes that cooperate with MYC to promote formation of G3-MB, we performed an in vivo mutagenesis screen using mice expressing the Sleeping Beauty (SB) transposon. Cerebellar stem cells from transposon/transposase-expressing mice were infected with viruses encoding Myc, and transplanted into the cerebellum of adult hosts. The resulting tumors were sequenced to identify transposon-targeted genes, and these genes were functionally analyzed to determine whether they could cooperate with Myc to drive G3-MB. These studies identified the transcription factor Ras-responsive element binding protein 1 (Rreb1) as a potent Myc-cooperating gene. Tumors driven by Myc and Rreb1 resemble G3-MB at a histological and molecular level. Moreover, RREB1 is overexpressed in human G3-MB, and knockdown of RREB1 impairs growth of G3-MB cell lines and patient-derived xenografts. Ongoing studies are aimed at identifying the mechanisms by which Rreb1 contributes to tumor growth. Our studies demonstrate an important role for RREB1 in G3-MB, and provide a new model that can be used to identify therapeutic targets and develop more effective therapies for medulloblastoma.